A comparison of concussion assessment and management protocols used by medical personnel at elite taekwondo tournaments in the Republic of Korea and the United States - Fife, G.; Harter, R. (Archives of Budo, 2012)
Background and Study Aim: Little is known about the assessment and management protocols used by taekwondo tournament medical personnel to evaluate concussions. The purpose of this study was to compare the methods used by medical personnel in the Republic of Korea and the United States to assess and manage concussions sustained at elite taekwondo tournaments. Material and Methods: Between 2006 and 2008, pencil-and-paper questionnaires were administered to 18 medical personnel providing sports medicine services at three national-level taekwondo tournaments in South Korea, and at one national-level taekwondo tournament in the United States. Results: Four of 11 South Korean medical personnel (36%) held registered nursing (RN) credentials, four were physical therapists (36%), and three (27%) were emergency medical technicians (EMTs). In comparison, 2 of 7 American medical personnel were physicians (29%), two were certified athletic trainers (29%), two were EMTs (29%), and one was a physical therapist (14%). Of the South Korean medical personnel, 55% had less than 1 year experience serving as medical providers at taekwondo tournaments. In contrast, 71% of the American medical practitioners had greater than or equal to 5 years of experience serving as medical personnel at taekwondo tournaments, with the majority reporting greater than 10 years of experience at national level taekwondo tournaments. Both groups reported using symptoms checklists and clinical examination as their principal methods of concussion assessment. Conclusions: We recommend that taekwondo national governing bodies only assign medical personnel who have extensive direct experience with the sport of taekwondo to provide medical services at national-level tournaments.